Vers une définition multidimensionnelle du risque - Céline Kermisch (VertigO)
The status of risk is intrinsically ambiguous and difficult to grasp both ontologically and epistemologically. The purpose of this paper is to clarify it through an analysis of the various conceptions of risk found in the literature. More precisely, the study of the realistic and the representational conceptions of risk leads to favour the representational ones. We show that the different representational conceptions – quantitative and constructivist – should be conceived as being complementary. We translate this complementarity by supporting a multidimensional definition of risk based on a quantitative component as well as on a qualitative one. This definition is open and contextual, in order to take into account the complexity and the specificity of each kind of risk in its context. Such a definition is helpful insofar as it restores the role of values and of qualitative criteria in a more global framework, which takes social pluralism into account and thereby helps ensuring an ethical risk management.